2011
DOI: 10.1111/j.1365-2605.2010.01136.x
|View full text |Cite
|
Sign up to set email alerts
|

SRD5A2 gene mutations and polymorphisms in Spanish 46,XY patients with a disorder of sex differentiation

Abstract: One hundred and forty-six index patients with 46,XY DSD in whom gonads were confirmed as testes were consecutively studied for a molecular diagnosis during the period 2002-2010. AR gene was analysed in all patients as the first candidate gene, yielding a mutation in 42.5% of cases and SRD5A2 gene was analysed as the second candidate gene, resulting in the characterization of 10 different mutations (p.Y91D, p.G115D, p.Q126R, p.R171S, p.Y188CfsX9, p.N193S, p.A207D, p.F219SfsX60, p.R227Q and p.R246W) in nine inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
(45 reference statements)
2
25
1
Order By: Relevance
“…In our series, all patients with SRD5A2 mutations presented the homozygous genotype V89/CC for two polymorphisms (rs523349: p.V89L and rs522638: c.281 + 15T>C) which has not been associated with hypospadias (Fernandez-Cancio et al, 2011), and, therefore, it cannot be involved in the phenotype.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In our series, all patients with SRD5A2 mutations presented the homozygous genotype V89/CC for two polymorphisms (rs523349: p.V89L and rs522638: c.281 + 15T>C) which has not been associated with hypospadias (Fernandez-Cancio et al, 2011), and, therefore, it cannot be involved in the phenotype.…”
Section: Discussionmentioning
confidence: 72%
“…SRD5A2 gene analysis was performed as indicated by Fernandez-Cancio et al (2011) in the same laboratory.…”
Section: Molecular Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In in vitro studies, the POR p.A503V variant decreased P450c17 catalytic activity in 60% of the population [25] but did not change P450c21 activity [26]. The SRD5A2 p.V89L allele reduced the conversion of testosterone into dihydrotestosterone in 30% of cases and was more frequent in males with disorders of sex development in comparison to controls [27]. Conversely, some variants are associated with increased androgen synthesis, with the HSD17B5 c.-71A>G allele increasing protein expression and determining a 20% increase in serum testosterone levels and an increased risk for polycystic ovary syndrome [19].…”
Section: Discussionmentioning
confidence: 99%
“…A study from our Dutch colleagues reported that 13/18 cases previously thought to have AIS were ultimately found to have mutations in HSD17B3 (9). Amalgamated data from the Dutch nationwide survey (1) and three Spanish reports (10,18,19) are shown in Fig. 2B, estimating diagnostic proportions among paediatric cohorts.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%